Rancang Bangun Sistem Aplikasi PPDB Berbasis Laravel Pada SMP Al-Amanah - Hakim, Hamdan Qo’du Ilal; Ilham, Farizi; Jumyarti; Safitri, Luthfi (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
The new student admission process (PPDB) in private school often faces administrative obstacles due to decentralized data management. SMP Al-Amanah currently relies on a semi-manual registration mechanism using Google Forms distributed partially via social media, making it difficult for prospective guardians to monitor registration status through a single portal. This study aims to design and build an adaptive and integrated web-based online PPDB application system at SMP Al-Amanah to optimize committee work efficiency and information transparency. The system development method used is the Waterfall model, encompassing requirement analysis, system design, program code implementation, and system testing. This application is built using the PHP programming language with the Laravel Framework and MySQL as the database management system. The designed system integrates 9 core features, including multi-stage digital form, document upload features with a preview function, admin verification modules, and payment gateway integration for administrative fee settlement. The functional testing result using the Black Box Testing method indicates that all application features run according to expectations with 100% success rate without functional errors. The implementation of this system successfully reduces data redundancy, accelerates the verification process of physical documents, and facilitates remote registration accessibility from home.